Comportamento ingestivo de novilhas Nelore em pastejo recebendo suplemento a base de própolis ou monensina sódica - Valerio Geron, Luiz Juliano; Zeoula, Lucia Maria; Yoshimura, Emerson Henri; Franco, Selma Lucy; Neto, Marcos Chiquitelli [UNESP]; Paula, Eduardo Marostegan; Samensari, Rafael Barreiros; Peres, Lucimar Pontara (Univ Estadual Londrina, 2014)
We evaluated the effect of additives the basis of propolis and monensin on ingestive behavior (grazing -GRA, rumination lying -RLY, rumination in foot -RFO, rumination -RUM; idleness lying -ILY, idleness in standing -IDS, idleness -IDL, walking -WAL, posture standing -POS, posture lying -PLY, intake of supplement and water -ISW) of heifers in Tifton 85 grazing. The treatments were: no additive (NAD); propolis - PRO (33.24 mg animal-1 of total flavonoid in apigenin), and monensin -MON (100 mg animal(-1)). Were used five heifers treatment(-1) for evaluation of ingestive behavior during 12 hours of total valuation, which was divided into three periods. Used a factorial design into 3 x 3 for evaluation of ingestive behavior as a function of the evaluation periods. Were utilized three paddocks of 2.9 acres of grass Tifton 85. The additives and mineral supplement (50 g animal(-1)) were provided with 200 g of corn meal to 17 hours. For all activities of the ingestive behaviors observed the effect of period on the time spent on of different activities. The activities of GRA and ISW were higher in the third period (15hours to 19hours) compared to the first period (7hours at 11hours). For IDL and PLY, there was a higher time in minutes for heifers treatment with PRO in the period of 7hours at 11hours, compared to other treatments (NAD and MON). Thus, it is concluded that the use of the additive based on propolis enables sodium monensin replacement, to heifers maintained on pasture without changing eating behavior as well as providing greater idleness during the day the without affecting animal performance.
Ingestive behavior of Nellore heifers grazing receiving the supplement based on propolis or monensin
Keywords: Idleness; grazing; ruminating; supplementation